Canopy nitrogen application effects on Quercus petraea L. and Fagus sylvatica L. ring width and wood density - Daniel Minikaev; Maurizio Ventura; Giustino Tonon; Enno Uhl; Dario Ravaioli; Przemysław A. Jankowski; Camilla Wellstein (European Journal of Forest Research, 2025)
As an essential nutrient, Nitrogen (N) availability is fundamental in evaluating forest productivity, and as such, understanding the effects of changing atmospheric N inputs in forest ecosystems is of high significance. While most field experiments have been employing ground fertilization as a method to simulate N deposition, two experimental forest sites in Italy have adopted the more advanced canopy N application approach. Here we present findings from a case study of wood core analyses of predominantly pure, even aged, Sessile oak ( Quercus petraea L. ) and European beech ( Fagus sylvatica L. ) forest stands, treated with either below or above canopy N fertilization, comparing between the two simulation pathways of increased N deposition. The potential effects of elevated N availability on total ring width, mean ring density, and their corresponding earlywood and latewood fractions are examined. Our results indicate inconclusive effects of the treatments on the ring width traits of both Q. petraea or F. sylvatica , although basal area increment patterns appeared to be affected divergently between the species and treatments. Mean and earlywood, but not latewood, densities on the other hand, exhibited a decrease in certain years of the treatment period in Q. petraea as result of the above canopy N application only, whereas F. sylvatica wood density showed no clear response to any of the treatments. Thus, we are describing distinct reactions of the two broadleaved species to the different experimental N deposition approaches, discussing potential growth patterns under increased N availability, and emphasizing the importance of considering wood density in assessments of tree biomass accumulation and essentially Carbon storage capacities.